Micro-environmental conditions and high population density affects the transmission of severe acute respiratory syndrome corona virus-2 in metropolitan cities of India - Sanjay Dwivedi; Seema Mishra; Ruchi Agnihotri; Vishnu Kumar; Pragya Sharma; Geetgovind Sinam; Vivek Pandey (Wolters Kluwer Medknow Publications, 2021)
Aim: The present study explores the effects of high population density (PD), climatic and environmental factors on transmission of coronavirus disease 2019 (COVID-19) in selected metropolitan cities of India. Materials and Methods: A data extraction sheet has been prepared to summarize the data of confirmed severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) cases and number of deaths in ten metropolitan cities, which was taken from Government of India website. The data on environmental factors of each selected metropolitan city were compiled from the official website and climatic conditions from Meteorological Department Government of India. Results: In India, maximum positive COVID-19 cases (>32%) has been found in tropical wet and dry climate zone. While the incidence of COVID-19 cases has been found less in the arid zone of India. Poor correlation has been found between level of Vitamin D, total COVID-19 cases, and mortalities in the studied metropolitan cities. No significant correlation was found between the health care index and COVID-19 cases and mortality. Conclusions: Correspondence and principal component analysis statistics showed high PD, poverty, climatic and environmental factors influenced the SARS-CoV-2 transmission in metropolitan cities of India.